Tiering effect of solid-core photonic crystal fiber on controlled coupling into multimode fiber - Yin, Shizhuo; Amphawan, Angela; Al Samman, Nashwan M. A.; Guo, Ruyan (2013)
To enhance the channel impulse response and signal quality through a multimode fiber, the incident wavefront into a multimode fiber may be controlled using phase masks, gratings and spatial light modulators.In this paper, an elegant technique for controlled coupling into a multimode fiber is demonstrated using a solid-core photonic crystal fiber to reduce differential mode delay in a multimode fiber.The increase in the number of tiers of a solid-core photonic crystal fiber is shown to reduce differential mode delay and improve the bit-error rate of a multimode fiber channel. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE).Downloading of the abstract is permitted for personal use only.